Avaliação do efeito protetor de queijo de coalho caprino na sobrevivência de uma nova cepa com potencial probiótico - Rolim, Fernanda Rodrigues Leite (2015)
The demand for foods with balanced nutritional composition and that may also provide additional health benefits is required by today's consumers. These are called functional food product, that includes the probiotics, i.e., foods added from cultures of micro-organisms which act as processing therapeutic agents. To provide benefits, these micro-organisms must be suitable to certain criteria such as survival throughout the gastrointestinal tract. Other criteria include non-toxic and non-pathogenic micro-organisms and ability to prevent or inhibit the growth of organisms harmful to health. Foods are considered as an ideal instrument for the supply of probiotics to the human gastrointestinal tract by a protective effect on the probiotic strains during passage to its site of action, the intestine. Thus, the micro-organisms must be compatible with the matrix product: processing, storage conditions, ingredients, physical and chemical properties and the presence of competing micro-organisms and inhibitors, to maintain viability and desired properties. Dairy products are the main food matrices supplemented with probiotics such as yogurt, fermented milks, cheeses, dairy beverages and dairy desserts. Cheese have advantages such as: high pH, increased buffering capacity, nutrient available, low oxygen content. In the review article, the present study approached features associated to probiotics emphasizing research related to the use of cheese as a matrix and evaluation in vitro or in vivo about the topic. This research also includes an article that evaluated the viability of Lactobacillus rhamnosus EM1107 that was added to semi-hard goat cheese (Coalho) when exposed to simulated gastrointestinal conditions. The inhibitory effects of this strain against pathogenic bacteria in goat Coalho cheese were also evaluated during 21 days of refrigerated storage. After in vitro digestion, no change in the viable cell count of L. rhamnosus (6.75 log CFU/g) was observed compared with the count before exposure to oral conditions (6.55 log CFU/g). When evaluated against S. aureus, L. rhamnosus exhibited the inhibition rates of 1.55%, 1.7% and 21.66% at 7, 14 and 21 days of storage, respectively. Furthermore, against Salmonella Enteritidis, the inhibition rates were 4.36%, 5.33% and 5.51% at 7, 14 and 21 days of storage, respectively; against Escherichia coli at 7 days of storage, the inhibition rate was 7.98%; and against Listeria monocytogenes, the inhibition rates were 2.62%, 1.57% and 10.23% at 7, 14 and 21 days of storage, respectively. These results indicate that goat Coalho cheese has a protective effect on the viability of L. rhamnosus EM1107 during artificial digestion. In addition, this strain could be used as a protective culture to delay the growth of pathogenic bacteria, particularly S. aureus and L. monocytogenes.